2000
DOI: 10.1080/713654979
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and immune response of two commercial broiler strains fed diets containing Lactobacillus cultures and oxytetracycline under heat stress conditions

Abstract: 1. Hubbard x Hubbard (HH) and Shaver x Shaver (SS) chicks given a dietary supplement of either 50 mg/kg oxytetracycline (OTC) or 1 g/kg Lactobacillus culture (LC) were exposed to 36 +/- 1 degrees C for 3 h daily from day (d) 21 to 42. 2. Prior to heat treatment, body weight (d 21) and weight gain (d 1 to d 21) of OTC and LC birds were greater than those fed the control diet. Chicks given LC had the best food efficiency followed by OTC and control birds during d 1 to d 21. Body weight (d 1 and d 21) and weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
140
3
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(172 citation statements)
references
References 30 publications
24
140
3
5
Order By: Relevance
“…In a heat stress study, Mashaly et al (2004) reported a decrease in antibody titres to sheep red blood cells in laying hens. These results agree with the findings of Zulkifli et al (2000), who showed that heat stress caused a reduction in antibody synthesis. Stressors increased serum corticosterone levels (Glaser & Kiecolt-Glaser, 2005;Quinteiro-Filho et al, 2010, 2012aShini et al, 2010), and this hormone inhibits antibody production by B cells (Gross, 1992), which might explain the inverse relationship we found between corticosterone levels and IgG titres.…”
Section: Discussionsupporting
confidence: 83%
“…In a heat stress study, Mashaly et al (2004) reported a decrease in antibody titres to sheep red blood cells in laying hens. These results agree with the findings of Zulkifli et al (2000), who showed that heat stress caused a reduction in antibody synthesis. Stressors increased serum corticosterone levels (Glaser & Kiecolt-Glaser, 2005;Quinteiro-Filho et al, 2010, 2012aShini et al, 2010), and this hormone inhibits antibody production by B cells (Gross, 1992), which might explain the inverse relationship we found between corticosterone levels and IgG titres.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings concerning the immunopotantiation caused by probiotic administration concur with Pollmann et al, (1980); Zulkifli et al, (2000); Toms and Powvie (2001) ;Huang et al, (2004); Koenen et al, (2004). Also, Sevage et al, (1996) and Panda et al, (2000) demonstrated an increase in the serum immunoglobulins IgG and IgA after administration of competitive exclusion cultures.…”
Section: Results Listed In Tablesupporting
confidence: 73%
“…on bird's performance in case of absence of enteric infections revealed that these compounds are effective as they improve the growth of the broiler chickens (Mohan et al, 1996;Jin et al, 1998;Zulkifli et al, 2000;Kalvathy et al, 2003;Gracia et al, 2004;Huang et al, 2004;Opalinski et al, 2007;Midilli et al, 2009). On the other hand, Angle et al, (2005) found no improvement in performance but there were increased protein, calcium and phosphorus retention.…”
Section: Contrary Results Were Mentioned Bymentioning
confidence: 98%
“…Lactic acid bacteria (LAB) living symbiotically in the digestive tract of birds were found to enhance the immunity of animals to pathogenic bacteria (Zulkifli et al, 2000). LAB have adhesive properties and can colonize different parts of the avian digestive tract (Jin et al, 1996).…”
Section: Introductionmentioning
confidence: 99%